THE EXTROVERT-INTROVERT PERSONALITY AND THEIR SECOND LANGUAGE ACQUISITION - Ni Made Diana Erfiani; Yohanes Octovianus Lesu Awololon; I Rai Hardika (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
Studying language requires more than a purely linguistic approach; it also necessitates examining the mental processes involved, which falls under the psychology domain. By addressing the question why some individual succeed in learning a second language while others fail, this study aimed at investigating how the extrovert-introvert personality acquired English as a second language. This study employed a descriptive qualitative approach through observations of the daily activities of six respondents at the Green Lion Bali Foundation and utilizeed a questionnaire to determine the respondents’ personality types. Interviews with colleagues were also used as a method of data triangulation for the research. The result of this study revealed that the influence of personality traits on English language acquisition, revealing different acquisition patterns. Extroverts, with their tendency toward openness, exhibit a more spontaneous language acquisition style. In contrast, introverts, who tended to be more reserved, display a more disciplined and structured language acquisition pattern, although they tended to communicate more slowly. Therefore individual’s tendency toward a dominant extroverted or introverted personality can significantly contribute to the creative learning process in English language acquisition.